DIGITAL MARKETING STRATEGY THROUGH SOCIAL MEDIA IN INCREASING THE SALES OF THE FLOWER BUCKET BUSINESS IN SERANG - Icin Quraysin; Ika Pratiwi; Andi Hasryningsih Asfar; Martinus Tukiran (Yayasan Education and Social Center, 2022)
A marketing Strategy is a series of integrated actions towards a sustainable competitive advantage. Meanwhile, marketing strategies and tips from the seller's point of view (4P) are a strategic place (place), quality product (product), competitive price (price) and vigorous promotion (promotion). Total customer satisfaction is the ultimate goal and marketing strategy concept (Total Customer Statistics). Flower bouquet marketing strategy by utilizing social media the study aims to find out how the marketing strategy for a digital flower bouquet business through social media is to increase sales and what are the obstacles and challenges to marketing flower bouquets by utilizing social media. The research method used is qualitative, The results of the study explain that increasing the sales results of flower bouquet entrepreneurs in Serang City with social media marketing strategy steps for small-scale businesses using WhatsApp, Instagram and Facebook, namely: social media marketing strategies by building credibility, attracting potential customers, building relationships on social media, sharing content, create valuable content, use good and interesting images, crowdsource interesting and authentic content, participate in online groups and communities, use social media as a space to have interesting conversations and limit social media platforms